Die statutere erkenning van inheemse reg gedurende die Britse administrasie van Tansvaal, 1877-1881 (Historia, 2021)
The statutory recognition of Native Law during the British Administration of the Transvaal, 1877-1881. Although the South African Republic had recognized native law in certain respects before the annexation of the Republic in 1877, the British administration of the Transvaal felt that no statutory recognition of native law existed and that the blacks should be governed in terms of the laws of the Republic in accordance with Roman Dutch Law or common law. In order to bring about a change in this regard Sir Theophi1us Shepstone, the administrator of Transvaal, set in motion attempts in May 1877 to make provision for a judicial system according to which blacks would be governed in accordance with their own laws and customs. However, because of a lack of the necessary 1egis1atsive authority, nothing could be achieved in this connection. In these circumstances and without statutory recognition having been given to native law, H.C. Shepstone, the Secretary for Native Affairs in Transvaal, introduced a number of measures in terms of which civil cases between blacks would be heard according to native law. In June 1880 the Native Administration Law was approved by the ugis1ative Council which gave statutory recognition to native law. As this law had to be reserved for the approval of the Crown before it could be proclaimed and also because of neglectful handling, the Native Administration Law was only proclaimed as Law No. 11 of 1881 in July 1881.
Keywords: Shepstone T.; Native Administration Law; Shepstone H.C.; Native law; Indigenous law; Transvaal